Innovative use of stabilized pond ash as a sustainable material for flexible pavements: Experimental, microstructural, and numerical investigations - Hrushikesh N. Kedar; Satyajit Patel (Next Materials)
This study investigates the use of pond ash stabilized with lime and ground granulated blast furnace slag (GGBS) as an eco-friendly subbase material for the base and subbase layer of flexible pavements. Laboratory evaluations, including unconfined compressive strength (UCS), resilient modulus (Mr), and microstructural assessments using X-ray diffraction and scanning electron microscopy, were carried out to analyze the performance of pond ash-lime-GGBS blends. The addition of lime and GGBS considerably improved the engineering properties, resulting in upper maximum dry unit weight and lower optimum moisture content compared to untreated pond ash. The optimum mix designs for subbase applications were determined to be 86PA+ 2 L+ 12 G and 88PA+ 3 L+ 9 G. Resilient modulus values of these mixes were approximately 61 % greater than those of traditional granular subbase material, enabling a reduction in subbase layer thickness without compromising pavement performance. XRD analysis revealed the formation of pozzolanic compounds, while SEM images confirmed improved particle bonding and reduced porosity in the treated mixes. Finite element analysis using PLAXIS 3D indicated that pavements incorporating the 88PA+ 3 L+ 9 G mix exhibited up to 83 % and 74 % longer service lives for fatigue and rutting failure standards, respectively, compared to GSB-based pavements. The findings also underscore the environmental and economic benefits of utilizing treated pond ash, offering a cost-effective and eco-friendly alternative to natural aggregates. This study demonstrates the viability of pond ash-lime-GGBS mixes as an innovative green supplementary material for sustainable road pavement construction.